2018
DOI: 10.3906/sag-1803-171
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of perindopril arginine and amlodipine on choroidal thickness in patients with primary hypertension

Abstract: Background/aim: This study aimed to investigate the effects of two different medical treatment options on choroidal thickness (CT) in patients with primary hypertension. Materials and methods: Forty newly diagnosed primary hypertension patients and 21 healthy volunteers were included. The patients were randomly divided into two subgroups. Group I started on perindopril arginine and Group II started on amlodipine. Submacular CT using optical coherence tomography (OCT) was measured before treatment and at the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(43 reference statements)
0
3
0
2
Order By: Relevance
“…Clinical researchers using OCT to examine RNFLT/GCIPLT in ocular disease should either exclude patients with systemic hypertension from the control group or statistically interpret the systemic vascular risk. 29 Failure to consider BP factors as potential confounders may bias the study results and lead to erroneous conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical researchers using OCT to examine RNFLT/GCIPLT in ocular disease should either exclude patients with systemic hypertension from the control group or statistically interpret the systemic vascular risk. 29 Failure to consider BP factors as potential confounders may bias the study results and lead to erroneous conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of patients treated for hypertension with either perindopril arginine (an angiotensin-converting enzyme inhibitor) or amlodipine (a calcium channel blocker) found that treatment with perindopril arginine reversed the choroidal thinning (suggesting an improvement and/ or reversal of vascular changes), whereas amlodipine use did not significantly affect the choroidal thickness. 29 Whether the inner retinal layer shows a similar response to that of the choroid needs to be investigated. Second, although people with pRNFL defects, glaucomatous neuropathy, and a history of an IOP of ≥21 mmHg were excluded, visual field examinations were not performed; therefore, we cannot completely exclude patients with preclinical glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…A small case-control study of 61 patients demonstrated that CT increases after a 6-month course of perindopril arginine 5 mg once daily, while administration of amlodipine 5 mg once daily had no significant effect. 43 Indirect evidence of the effect of BP control on CT also emerges from a small cohort of type 2 diabetes mellitus (T2DM) patients undergoing intensive diabetic control. Intensification of antihypertensive drugs in order to achieve BP below 130/80 mmHg was part of the protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Dikkat ve özen yükümlülüğünün kaynaği olan davraniş normlari pozitif hukuk kurallariyla düzenlenmektedir. Belirtelim ki dikkat ve özen yükümlülüğü kanundan kaynaklansa da bu yükümlülüğün yerine getirilmesi noktasinda alinacak olan tedbirlerin neler olduğunun her zaman için kanunda düzenlenmiş olmasi beklenmemektedir 55 . Taksirin tespiti bakimindan önem arz eden bir diğer nokta ise öngörülebilir olan bir unsurun öngörülmemiş olmasidir.…”
Section: Taksirli Suçlardaunclassified
“…Taksirin tespiti bakimindan önem arz eden bir diğer nokta ise öngörülebilir olan bir unsurun öngörülmemiş olmasidir. Belirtmek gerekir ki öngörülebilirlik kişilere yüklenmiş olan dikkat ve özen yükümlülüğünün doğal bir sonucu olarak karşimiza çikmaktadir 56 . Bunun yaninda failin taksirli suçtan sorumluluğunun doğabilmesi için kendi yetenekleri, algilama gücü, tecrübeleri, bilgi düzeyi ve içinde bulunduğu koşullar altinda, objektif olarak var olan dikkat ve özen yükümlülüğünü öngörebilecek 57 ve yerine getirebilecek durumda olmasi da aranmaktadir.…”
Section: Taksirli Suçlardaunclassified